Civilizing disability society : the Convention on the Rights of Persons with Disabilities socializing grassroots disabled persons organizations in Nicaragua / Stephen J. Meyers. - Meyers, Stephen J., 1976- (Cambridge disability, law and policy series., 2019)
The United Nations Convention on the Rights of Persons with Disabilities (CRPD) is increasingly used to civilize grassroots disabled persons' organizations (DPOs) around the world. The international disability rights movement actively promotes the CRPD's key norm that disabled persons mobilize in support of their rights under the Convention. The unintended consequence of these activities, however, is that local groups focused on social support and service provision, rather than disability-rights advocacy, are targeted for change. While the resources provided by international actors to grassroots organizations provide new opportunities, they also create barriers to local groups' ability to promote full civic participation of their members in the local community. Through a detailed account of grassroots DPOs in Nicaragua, Civilizing Disability Society demonstrates how local organizations navigate pressures from abroad as they attempt to concretely address the health, education and economic needs of their members at home.